Laparoscopic ventral mesh rectopexy in complex pelvic floor disorder - Horisberger, Karoline; Rickert, Alexander Lothar; Templin, Stefan; Post, Stefan; Kienle, Peter (International journal of colorectal disease, 2016)
AimFor the treatment of complex pelvic organ prolapse, many different surgical procedures are described without any comparative studies available. Laparoscopic ventral mesh rectopexy after D’Hoore is one of the methods, which is publicized to treat patients with symptomatic rectocele, enterocele and rectal prolapse.MethodAll patients who received ventral mesh rectopexy since 07/10 for symptomatic rectocele, enterocele and possible rectal prolapse I ° or II ° in terms of a complex pelvic floor disorder were included in this follow-up study. The Wexner score for incontinence was recorded (range 0-20), the constipation score of Herold (r6-30) was evaluated as well as supplementary questions compiled by D’Hoore concerning outlet symptoms (r0-20). In addition, the quality of life (SF-12) was requested.ResultsThirty-one women were operated in the period, and 27 were eligible to be included in the present study. Median follow-up was 22 months (2-39). The preoperative Wexner score was in median 8 (0-20), going down to 6 (0-20) without significance (p = 0.735). The constipation score decreased significantly from median 14 (9-21) to 11 (6-25) (p = 0.007). The median score after D’Hoore was preoperatively 8 (4-16) and 4.5 (0-17) postoperatively (p = 0.004). The SF-12 values were preoperatively significantly reduced compared to the normal population; postoperatively, they equalized.ConclusionTwo years after laparoscopic ventral mesh rectopexy, constipation and quality of life improve significantly in patients with complex pelvic organ prolapse. The grade of incontinence remains essentially the same, but was not the dominant clinical problem in the treated patients of our study.StatementThe improvement in constipation and quality of life after laparoscopic ventral mesh rectopexy for obstructive defecation is encouraging. However, the impact on sexual life differs; some patients improve but a relevant number reports a change for the worse.
Gesehen am 07.05.2019